The Effect of Talking Stick Type Cooperative Learning Model on the Mathematics Learning Outcomes of Grade III Students - Endang Manurung; Theresia Monika Siahaan; Osco Parmonganan Sijabat (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research aims For Know The Influence of Learning Models Cooperative Talking Stick Types on Learning Outcomes Mathematics Grade III Students Uptd Sd Negeri 122399 Pematangsiantar. This research is studies quantitative as well as design pre-experimental, type design pre -test – post -test group. This design utilized because there is testing in form pre - test, implemented before treatment and post -test were given after treatment as well as utilizing working models The same Based on discussion in chapter this, researcher explain structure problems and hypotheses submitted as well as conclusion withdrawn start of study output obtained, then all over activity study discussed about impact of teaching models cooperative. Impact of teaching models cooperative towards teaching output Mathematics in Class III UPTD SD N 122399 Pematang Siantar is as as follows: Based on the output of the study by eye lessons in Class III UPTD SD N 122399 Pematang Siantar, the average pre-test score in content Mathematics " Measuring Length and Unit Standard " is 33.28 Not reached KKTP value of 70Use of facilities Talking Stick teaching UPTD SD N 122379 Pematang Sanator by eye lesson Mathematics in Class III reached increased learning output as well as the average post-test value is the number reached 85.28 and KKTP was 70. Based on the experimental output implemented and data analysis, test output hypothesis in study This prove existence impact significant. start data checked, can obtained total t count = 27,107 levels the significance (2-tailed) is 0.000, the probability significant <0.05, t count > t table = 27.107 > 1.708, then Ho is rejected and Ha is accepted. Therefore it can concluded amount there is impact types of teaching models cooperative. UPT DSDN 122399 Tongkat talk by the learning output of grade III Pematang students Siantar